Pediatric examination & board review - Robert S. Daum; Jason J. Canel (McGraw-Hill Medical Pub. Division, 2007)
Pediatric Examination and Board Review is the best resource for preparing for examinations and boards. It employs a step-by-step approach to case-based learning that assures more thorough absorption of material, and reinforces your understanding of even the most difficult topics. Coverage reflects all recent advances of clinical importance, so you can assimilate the critical new information easily into your examination preparation activities and daily practice. It's the ultimate tool to prepare for certification and recertification/maintenance of certification, or for use as a clinical refresher!